5
-5
-15
Answer: second option.
Step-by-step explanation:
Let be "x" the unknown number.
According to the information provided in the exercise, 10 is the result of the subtraction of "x" and -5.
Based on this, you can write the following equation:
To find the value of "x" you must remember the multiplication of signs:
Then:
Finally, subtracting 5 from both sides of the equation, you get:
Answer:
x - (-5) = 10
x = 5
My final answer is 5
Step-by-step explanation:
There are 15 oranges
Solution:
Let "x" be the number of oranges
Let "y" be the number of pears
Let "c" be the number of children
There are 3 times as many pears are oranges
Number of pears = 3 times the number of oranges
y = 3x -------- eqn 1
If a group of children receive 5 oranges each, there will be no left over
So, "c" children receives 5 oranges each, there will be no left over
number of oranges = 5(number of children)
x = 5c ------- eqn 2
If the same group of children receive 8 oranges each, there will be 21 pears left over
number of pears = 8 oranges(number of children) + 21
y = 8c + 21
Substitute eqn 1
3x = 8c + 21 ---- eqn 3
Substitute eqn 2
3(5c) = 8c + 21
15c - 8c = 21
7c = 21
c = 3
Substitute c = 3 in eqn 2
x = 5(3)
x = 15
Thus there are 15 oranges
Answer:
15 orangs
Step-by-step explanation:
There are 15 oranges
Solution:
Let "x" be the number of oranges
Let "y" be the number of pears
Let "c" be the number of children
There are 3 times as many pears are oranges
Number of pears = 3 times the number of oranges
y = 3x -------- eqn 1
If a group of children receive 5 oranges each, there will be no left over
So, "c" children receives 5 oranges each, there will be no left over
number of oranges = 5(number of children)
x = 5c ------- eqn 2
If the same group of children receive 8 oranges each, there will be 21 pears left over
number of pears = 8 oranges(number of children) + 21
y = 8c + 21
Substitute eqn 1
3x = 8c + 21 ---- eqn 3
Substitute eqn 2
3(5c) = 8c + 21
15c - 8c = 21
7c = 21
c = 3
Substitute c = 3 in eqn 2
x = 5(3)
x = 15
Thus there are 15 oranges
Equation B: 2x + 4z = 1
Which of the following is a possible step used in eliminating the z-term?
Multiply equation B by 4.
Multiply equation A by 2.
Multiply equation A by –4.
Multiply equation B by 2.
Answer:
To eliminate the z-term, you need to multiply equation A by -4.
Step-by-step explanation: